1980
DOI: 10.1021/np50007a001
|View full text |Cite
|
Sign up to set email alerts
|

Recent Biosynthetic Studies on Antibiotics

Abstract: During recent years our re-earch group ha. been engaged in biobynthetic studies dealing Tt-ith antibiotic, of two different sort>. In a continuing qtudy we have investigated the biosynthetic origin. of the very important aminocyclitol antibiotics, which include gentamicin. neomycin, streptomycin, -pectinoniycin, etc. This topic has been reriened extensively vithin the past \- ear (1. 2 . 3). E-AMINOACETOPHENONEFIG. 2. Blternative biosynthetic pathxays t o m-aminoacetophenone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…This functional group is lost during the formation of the 2-oxazolidone ring structure present in the pactamycate derivatives. [9,23] To further evaluate and compare the in vitro efficacy of de-6-MSA-pactamycin with that of pactamycin, dose-response experiments were done by using a broth microdilution method with 0.01 (or 0.1)-100 mm concentrations of pactamycin and de-6-MSA-pactamycin ( Figure 7). In all of the studies, de-6-MSA-pactamycin showed equivalent biological activity with the parent molecule, pactamycin; this suggests that the 6-MSA moiety is not essential for activity.…”
Section: Inactivation Of Ptmq and Metabolic Analysis Of Ptmq A C H T mentioning
confidence: 99%
See 2 more Smart Citations
“…This functional group is lost during the formation of the 2-oxazolidone ring structure present in the pactamycate derivatives. [9,23] To further evaluate and compare the in vitro efficacy of de-6-MSA-pactamycin with that of pactamycin, dose-response experiments were done by using a broth microdilution method with 0.01 (or 0.1)-100 mm concentrations of pactamycin and de-6-MSA-pactamycin ( Figure 7). In all of the studies, de-6-MSA-pactamycin showed equivalent biological activity with the parent molecule, pactamycin; this suggests that the 6-MSA moiety is not essential for activity.…”
Section: Inactivation Of Ptmq and Metabolic Analysis Of Ptmq A C H T mentioning
confidence: 99%
“…[7] Pactamycin (1) consists of a five-membered ring aminocyclitol unit, which is rich in stereogenic centers, two aromatic rings (6-methylsalicylic acid (6-MSA) and 3-aminoacetophenone) and a 1,1-dimethylurea. [8,9] This compound showed potent antibacterial activities against Gram-positive and Gramnegative bacteria, [3] as well as strong anti-tumor activity. [3] However, its development as an antibiotic or an anticancer drug was hampered by its high toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These showed efficient incorporation of 2301 The five thiazole rings would be predicted to arise from a molecule of cysteine plus the carboxyl group of another acid or amino acid. This expectation is confirmed by the finding that ~,~-[3-'~C]cysteine labels C-5 in all the thiazole rings as well as C-3 in the cysteine moiety.…”
Section: Biosynthesis Of Nosiheptidementioning
confidence: 99%
“…Since nosiheptide 78 is evidently a modified peptide, the incorporation of a variety of 14C-labeled amino acids was tested in a series of preliminary feeding experiments 2301 The five thiazole rings would be predicted to arise from a molecule of cysteine plus the carboxyl group of another acid or amino acid. This expectation is confirmed by the finding that ~,~-[3-'~C]cysteine labels C-5 in all the thiazole rings as well as C-3 in the cysteine moiety.…”
Section: Biosynthesis Of Nosiheptidementioning
confidence: 99%